An Euler characteristic for modules of finite G-dimension - Sather-Wagstaff, Sean; White, Diana (MATHEMATICA SCANDINAVICA, 2008)
We extend Auslander and Buchsbaum’s Euler characteristic from the category of finitely generated modules of finite projective dimension to the category of modules of finite G-dimension using Avramov and Martsinkovsky’s notion of relative Betti numbers. We prove analogues of some properties of the classical invariant and provide examples showing that other properties do not translate to the new context. One unexpected property is in the characterization of the extremal behavior of this invariant: the vanishing of the Euler characteristic of a module M of finite G-dimension implies the finiteness of the projective dimension of M. We include two applications of the Euler characteristic as well as several explicit calculations.